Status and correlates of food and nutrition literacy among parents-adolescents’ dyads: findings from 10 Arab countries - Hoteit, Maha; Mansour, Rania; Mohsen, Hala; Bookari, Khlood; Hammouh, Fadwa; Allehdan, Sabika; AlKazemi, Dalal; Al Sabbah, Haleama; Benkirane, Hasnae; Kamel, Iman; Qasrawi, Radwan; Tayyem, Reema; et al. (Frontiers in Nutrition, 2023)
Background: Food literacy is capturing the attention worldwide and gaining traction in the Arab countries. Strengthening food and nutrition literacy among Arab teenagers are important promising empowering tools which can protect them from malnutrition. This study aims to evaluate assess the nutrition literacy status of adolescents with the food literacy of their parents in 10 Arab countries. Methods: This cross-sectional study involving a convenient sample of 5401 adolescent-parent dyads (adolescents: mean age ± SD: 15.9 ± 3.0, females: 46.8%; parents: mean age ± SD: 45.0 ± 9.1, mothers: 67.8%) was launched between 29 April and 6 June 2022 in 10 Arab nations. The Adolescent Nutrition Literacy Scale (ANLS) and the Short Food Literacy Questionnaire (SFLQ) were used to meet the study aims. Results: More than one-quarter (28%) of adolescents had poor nutrition literacy, with 60% of their parents being food illiterate. The top three countries with nutritionally ”less literate” adolescents were Qatar (44%), Lebanon (37.4%), and Saudi Arabia (34.9%). Adolescents’ age, gender, education level, primary caregivers, employment status, and the inclusion of nutrition education in the schools’ curriculum predicted the nutrition literacy levels of Arab adolescents. Besides, parental weight status, health status, parent’s food literacy level, and the number of children per household were significant determinants too. Adolescents studying at a university and having parents with adequate food literacy had the highest odds of being nutritionally literate (OR= 4.5, CI=1.8-11.5, p=0.001, (OR=1.8, CI=1.6-2.1, p<0.001, respectively). Conclusion: Nutrition literacy inadequacy among Arab adolescents is a prioritized challenge to be tackled.